Nekateri pojavi plesnega folklorizma v Beli krajini do 2. svetovne vojne - Kunej, Rebeka (Traditiones (Ljubljana), 2004)
The origin and the development of dance folklorism in Bela krajina has been greatly influenced by different events in which local inhabitants demonstated the dance heritage of the region. Examined are some of the events taking place prior to the Second World War that had a strong impact upon the birdh of dance folklorism in the area
Keywords: etnomuzikologija; ljudski plesi; Bela krajina; White Carniola; Slovenia; Slovenija